Empathy-Related Brain Activity in Somatosensory Cortex Protects From Tactile Priming Effects: A Pilot Study - Schaefer, Michael; Cherkasskiy, Lillia; Denke, Claudia; Spies, Claudia; Song, Hyunjin; Malahy, Sean; Heinz, Andreas; Ströhle, Andreas; Schäfer, Michael; Mianroudi, Nadine; Bargh, John A. (Frontiers in Human Neuroscience, 2020)
Empathic concerns influence how we perceive, understand, and interact with our social environment. Previous studies suggested a network of different brain regions as a neural substrate for empathy, including, in particular, insula and anterior cingulate cortex (ACC). In addition, a contribution of the somatosensory cortices for this empathy related network has been suggested. This is remarkable given that other recent studies have revealed a role for the somatosensory cortex in various social tasks. For example, in experiments using tactile priming, incidental haptic sensations are found to influence judgment recommendations. Here we aimed to test if this engagement of the somatosensory cortices during tactile priming can be predicted by the participant’s empathy personality traits. We assessed participant’s empathy and personality traits by means of the Interpersonal Reactivity Index (IRI) and NEO-FFI and tested whether trait empathy is associated with the tactile priming effect in social judgments. Results revealed that empathy predicted the tactile priming effect negatively. This was accompanied by a reduced engagement of the somatosensory cortex, which has been shown to be associated with the priming effect. We conclude that empathy seems to protect people from tactile priming effects.